2022
DOI: 10.21014/acta_imeko.v11i3.1269
|View full text |Cite
|
Sign up to set email alerts
|

Twisted and coiled polymer muscle actuated soft 3D printed robotic hand with Peltier cooler for drug delivery in medical management

Abstract: Many robotic hands have been proposed to have unique designs and capabilities, focusing on sensing, actuation, and control. This paper presents experimental studies on a soft 3D-printed robotic hand whose fingers are actuated by twisted and coiled polymer (TCP<sub>FL</sub>) muscles, driven by resistive heating, and cooled by water and Peltier mechanism (thermoelectric cooling) for increasing the actuation frequency. The hand can be utilized for pick and place applications of drugs in clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…TCP actuators are suitable for tasks which do not require a high-response frequency. Employing active cooling methods, such as fan cooling and liquid cooling or Peltier cooling, is a good choice to improve the response speed [30][31][32]. Future works should concentrate on improving the cooling speed.…”
Section: A Study On the Application Of Pid Control System For 6-ply T...mentioning
confidence: 99%
“…TCP actuators are suitable for tasks which do not require a high-response frequency. Employing active cooling methods, such as fan cooling and liquid cooling or Peltier cooling, is a good choice to improve the response speed [30][31][32]. Future works should concentrate on improving the cooling speed.…”
Section: A Study On the Application Of Pid Control System For 6-ply T...mentioning
confidence: 99%
“…Lamuta et al 38 showed soft morphing skins creating digital texture patterns. In order to increase the actuation frequency of the electrothermal TCP actuators Singh et al 39 introduced the Peltier coolers for improving the actuation frequency of the TCP FL actuated robotic hand. Earlier, Besse et al 40 demonstrated a flexible active skin with large reconfigurable arrays of shape memory polymer actuators.…”
Section: Introductionmentioning
confidence: 99%